2018
DOI: 10.1128/aac.00161-18
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Macrolide-Induced Inhibition of Pneumolysin Release Involves Impairment of Autolysin Release in Macrolide-Resistant Streptococcus pneumoniae

Abstract: is a leading cause of community-acquired pneumonia. Over the past 2 decades, macrolide resistance among organisms has been increasing steadily and has escalated at an alarming rate worldwide. However, the use of macrolides in the treatment of community-acquired pneumonia has been reported to be effective regardless of the antibiotic susceptibility of the causative pneumococci. Although previous studies suggested that sub-MICs of macrolides inhibit the production of the pneumococcal pore-forming toxin pneumolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Determination of neutrophil numbers by flow cytometry. To obtain BALF, 1.0 mL PBS was instilled into mouse lungs and then slowly aspirated (3,71). Single-cell suspensions from harvested gingival tissue were prepared according to a previously described method (75).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of neutrophil numbers by flow cytometry. To obtain BALF, 1.0 mL PBS was instilled into mouse lungs and then slowly aspirated (3,71). Single-cell suspensions from harvested gingival tissue were prepared according to a previously described method (75).…”
Section: Methodsmentioning
confidence: 99%
“…Macrolides have well-established antimicrobial and antivirulence effects that can be used to treat infectious diseases (1,2). For instance, we previously demonstrated that, in the context of macrolide-resistant Streptococcus pneumoniae (S. pneumoniae) infection, subminimum inhibitory concentrations of macrolides inhibit the release of pneumococcal autolysin, thereby preventing cell lysis and pneumolysin release (3). However, macrolides are also applied to treat noninfectious diseases, such as cystic fibrosis (4), chronic obstructive pulmonary disease (COPD) (5,6), acute respiratory distress syndrome (7), and certain forms of asthma (8).…”
Section: Introductionmentioning
confidence: 99%
“…S. mutans MT8148, S. sobrinus MT10186, MRSA NILS1, and methicillin‐sensitive S. aureus (MSSA) NILS6 were grown in brain heart infusion broth (Becton Dickinson, Franklin Lakes, NJ, USA) for 24 hr, as described previously . Macrolide‐resistant S. pneumoniae NU4471 (azithromycin MIC ≄ 1 mg/mL) was isolated from patients with respiratory tract infections . Macrolide‐and fluoroquinolone‐resistant S. pneumoniae KM279 (azithromycin and levofloxacin MICs of >8 and >8 ÎŒg/mL, respectively) and multidrug‐resistant S. pneumoniae KM256 (penicillin G, ceftriaxone, azithromycin, and levofloxacin MICs of >8, 8, 4, and >8 ÎŒg/mL, respectively) were isolated from children with acute otitis media .…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Macrolide-resistant S. pneumoniae NU4471 (azithromycin MIC ≄ 1 mg/mL) was isolated from patients with respiratory tract infections. 27 Macrolide-and fluoroquinolone-resistant S. pneumoniae KM279 (azithromycin and levofloxacin MICs of >8 and >8 ÎŒg/mL, respectively) and multidrug-resistant S. pneumoniae KM256 (penicillin G, ceftriaxone, azithromycin, and levofloxacin MICs of >8, 8, 4, and >8 ÎŒg/mL, respectively) were isolated from children with acute otitis media. 19 These clinical pneumococcal isolates and antibiotic-susceptible S. pneumoniae D39 were grown in tryptic soy broth (Becton Dickinson) for 12 hr.…”
Section: Bacterial Culture and Reagentsmentioning
confidence: 99%
“…S3A ). Barring occasional isolations of organisms coharboring different carbapenemase genes ( 13 , 14 ), few studies have shown the coexistence of two identical carbapenemase genes on different plasmids within an isolate ( 15 ). WGS revealed that isolate E119 carried pKPI-6 and an IncF-type plasmid (pEC743_1) that had a bla IMP-6 cassette from pKPI-6 integrated ( 49 ) (see Fig.…”
Section: Resultsmentioning
confidence: 99%